JCML: A specification language for the runtime verification of Java Card programs - Moreira, Anamaria Martins (2012)
COSTA, Umberto Souza; MOREIRA, Anamaria Martins; MUSICANTE, Matin A.; SOUZA NETO, Plácido A. JCML: A specification language for the runtime verification of Java Card programs. Science of Computer Programming. [S.l]: [s.n], 2010.